PERANCANGAN STRATEGI PEMELIHARAAN DENGAN PENDEKATAN METODE CMMS DAN OMMP DENGAN FMECA SEBAGAI PERSPEKTIF: (STUDI KASUS: INSTRUMENT AIR COMPRESSOR PT. XYZ) - Fauzi, Moh Hilal; Hariastuti, Ni Luh Putu (Universitas Nusantara PGRI Kediri, 2025)
PT. XYZ is an upstream oil and gas company that has been operating for more than 25 years. In the operation process on the platform, the power sources used are electricity and compressed air as a power source for instrumentation equipment. The compressed air power source here uses two instrument air compressor units. In 2023 to July 2024, this unit often experienced failures which resulted in high repair activities and unscheduled work. By using the OMMP method to measure maintenance performance, it can be seen that the coverage of the PM and PDM schedules is quite good, maintenance costs are low and under control. However, frequent unit failures result in high emergency work activities and make the equipment availability value low. The factors causing failure identified through FMECA are short circuits in the unit, loose terminals and high ambient temperature. Placing the unit outdoors is a factor that needs to be considered because the weather in the offshore area is quite extreme hot or when it rains. Several steps are proposed to prevent this from happening again, such as adding shelters, but still paying attention to air circulation to prevent overheating. With the CMMS method, the maintenance process can be carried out more quickly and accountably because the administration process can be carried out quickly, and maintenance recording can be done properly.